Peningkatan Pengetahuan dan Kesadaran Lingkungan Masyarakat Melalui Seminar dan Evaluasi Kuesioner di Desa Rejosari Barat - Prasetyawan Aji Sugiharto; Ismi Islamia R Iswari; Yan Imam Santoso; Muhammad Reza Ainun Najib; Dina Afriyana Solikhah; Najma Sakinatuzzulfia; Sa’adatun Saffanah; Eva Ayu Lestari; Laylatul Fatma; Rosalidya Putri (Abdimas Indonesian Journal, 2026)
The purpose of this community service activity was to raise awareness among the people of West Rejosari Village about the importance of environmental preservation in response to the low level of environmental awareness and improper waste management practices commonly found in rural areas through seminars and outreach. An interactive seminar designed as an educational counseling activity with speakers from the Batang Regency Environmental Agency was conducted, incorporating interactive discussions, question-and-answer sessions, and basic household waste management practices. The activity involved 19 participants consisting of women from the Family Welfare Movement (PKK), youth from the Youth Organization (Karang Taruna), and local community leaders. Evaluation was carried out using a structured questionnaire with yes/no indicators. The results showed that all respondents (100%) stated that the material was easy to understand, clearly delivered, relevant to their daily lives, and provided new environmental knowledge. Participants also reported increased motivation to adopt environmentally friendly behaviors and greater concern for environmental issues. Although the number of participants was limited, these findings indicate that seminar-based environmental counseling contributes practically to improving community knowledge and awareness of environmental conservation.